Analisis Kinerja Keuangan Bank Umum Syariah Di Indonesia Pada Masa Pandemi Covid 19 - Meisya, Hana; Pratama, Nuryanti (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to analyze the financial performance of Islamic Commercial Banks in Indonesia during the Covid-19 pandemic. The method used in this study is to use a quantitative type with secondary data in the form of panel data in the form of NPF, FDR, BOPO, and CAR ratios. The data source used uses quarterly financial reports for 2019-2020. The population in this study are all Islamic Commercial Banks in Indonesia that are registered with the Financial Services Authority (OJK) for the 2019-2020 period. In taking the sample of this study using purposive sampling technique. The results of this study indicate a significant change in the CAR, NPF and BOPO ratios of Islamic Commercial Banks before and during the Covid-19 pandemic. However, for the FDR of Islamic Commercial Banks during the Covid-19 pandemic there was change.